Сognitive Сomplaints with Unilateral Temporal Lobe Compression - M.U. Kaverina; U.V. Strunina; O.A. Krotkova (Клиническая и специальная психология)
Awareness of cognitive deficits, as a rule, occurs in the form of «memory complaints». Spontaneous narration of problems reveals their semantic hierarchy and can be a model for generating a spontaneous flow of thoughts and memories with the activity of the default brain network. The objective of the study was to study the nature of spontaneously expressed complaints about memory by patients with mild compression of the temporal regions of the resting network of the brain. The study was conducted in a homogeneous clinical group of 48 patients with extracerebral benign neoplasms located in close proximity to the medio-basal parts of the left (25 people) or right (28 people) temporal lobe. The tumor compresses these parts, but does not infiltrate the brain substance. With left-sided compression, complaints about verbal processes dominated, and their quantitative predominance over similar complaints was recorded in the group with right-sided compression and in the control group of healthy subjects (24 people). The severity of cognitive complaints with left-sided exposure to the brain revealed a negative correlation with experimental indicators of the success of spatial distribution of attention and simultaneous perception. With right-sided compression, spontaneously generated cognitive complaints revealed a dependence on the number of recognition errors in the AVP test, but this dependence was paradoxical: the worse this memory indicator was, the fewer cognitive complaints patients presented. The phenomenology of neural network compression makes it possible to register hemispheric specificity in spontaneously generated thoughts and memories.